An evaluation of interrupted and uninterrupted measurement of vocal stereotypy on perceived treatment outcomes. Issue 2 (25th April 2014) - Carroll, Regina A.; Kodak, Tiffany
<x xml:space="preserve">Abstract</x> The type of procedure used to measure a target behavior may directly influence the perceived treatment outcomes. In the present study, we examined the influence of different data‐analysis procedures on the outcomes of two commonly used treatments on the vocal stereotypy of 2 children with an autism spectrum disorder. In Study 1, we compared an interrupted and uninterrupted data‐analysis procedure to measure vocal stereotypy during the implementation of response interruption and redirection (RIRD). The results showed that the interrupted data‐analysis procedure overestimated the effectiveness of RIRD. In Study 2, we examined the influence of different data‐analysis procedures on the interpretation of the relative effects of 2 different treatments for vocal stereotypy. Specifically, we compared interrupted and uninterrupted data‐analysis procedures during the implementation of RIRD and noncontingent reinforcement (NCR) as a treatment for vocal stereotypy. The results showed that, as in Study 1, the interrupted data‐analysis procedure overestimated the effectiveness of RIRD; however, this effect was not apparent with NCR. These findings suggest that different types of data analysis can influence the perceived success of a treatment.